1984
DOI: 10.1002/qua.560260724
|View full text |Cite
|
Sign up to set email alerts
|

First principles charge transfer exciton theory of theUV spectrum of DNA

Abstract: The Slater-Koster resolvent formalism of exciton theory, as proposed originally by Takeuti, has been applied to calculate charge transfer exciton states and to investigate hypochromism in polynucleotides. As a first step, spatially well localized ab initio Wannier functions (WFS) are calculated at the Hartree-Fock level using a two-phase (inter-and intramolecular) localization procedure for the Fourier transformation of the Bloch functions. The single particle energies, entering the Green's function of the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Most of these methods use the Green's function formalism, [14][15][16][17][18][19][20] including MP2-based quasiorbital approaches. 7,[21][22][23][24] Periodic CIS and time dependent HF (TD-HF) methods and their DFT counterparts (TDA, TD-DFT) have been formulated 25 and implemented for 1D periodic systems. 21,[25][26][27][28][29] The periodic CIS treatment has been complemented with schemes, allowing for a low level inclusion of correlation effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these methods use the Green's function formalism, [14][15][16][17][18][19][20] including MP2-based quasiorbital approaches. 7,[21][22][23][24] Periodic CIS and time dependent HF (TD-HF) methods and their DFT counterparts (TDA, TD-DFT) have been formulated 25 and implemented for 1D periodic systems. 21,[25][26][27][28][29] The periodic CIS treatment has been complemented with schemes, allowing for a low level inclusion of correlation effects.…”
Section: Introductionmentioning
confidence: 99%
“…7,[21][22][23][24] Periodic CIS and time dependent HF (TD-HF) methods and their DFT counterparts (TDA, TD-DFT) have been formulated 25 and implemented for 1D periodic systems. 21,[25][26][27][28][29] The periodic CIS treatment has been complemented with schemes, allowing for a low level inclusion of correlation effects. 21,22 The most elaborate scheme within the theoretical description of excited states in periodic systems presently is EOM-CC theory with periodic boundary conditions, which was applied to polyethylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we have left out these results from Table I, Turning to the problem of the UV spectrum of DNA one should mention that the single nucleotide bases T, A, G, and C have as experimental first singlet excitation energies 4.67, 4.75, and 4.61 eV [30]. On the other hand there is an intermediate exciton band structure calculation for the C stack [31] using the 6-31G basis set and MP2 method for the correlation corrections of the band structure. According to the results obtained, the lower edge of the first singlet exciton band is at 4.7 eV and its upper edge at 5.4 eV (the corresponding values for the second singlet exciton band are at 5.9 and 6.2 eV, respectively) [31].…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand there is an intermediate exciton band structure calculation for the C stack [31] using the 6-31G basis set and MP2 method for the correlation corrections of the band structure. According to the results obtained, the lower edge of the first singlet exciton band is at 4.7 eV and its upper edge at 5.4 eV (the corresponding values for the second singlet exciton band are at 5.9 and 6.2 eV, respectively) [31]. In any event, this investigation has shown that there occur exciton bands in the spectra of the base stacks that are several eV broad.…”
Section: Resultsmentioning
confidence: 99%